The influence of physical properties on comfort performance of bedsheet fabrics - Nasir, Hana; Huzaisham, Nur Athirah; Mahmood, Salwa; Marsi, Noraini; Abdul Rashid, Azrin Hani; El Bakri, Helmy Mustafa; Misnon, Mohd Iqbal (IAEME Publication, 2020)
This paper analyzes the comfort performance of different types of bedsheet fabrics which are polyester, polyester blended with Tencel, cotton, Tencel and modal. The objectives of this study are to determine the physical and comfort properties of bedsheet fabrics as well as to evaluate the influence of physical properties on the comfort performance of bedsheet fabrics. The preparation of samples involved sourcing the fabrics that are commercially used. Physical properties such as thickness, mass per unit area and porosity were determined in order to evaluate their relationship on comfort properties such as thermal resistance, wicking area and water vapour transmission rate (WVTR). It was found that Tencel fabric exhibited the lowest thermal resistance of 0.0037 m2 °C/W while polyester fabric showed the highest thermal resistance of 0.0084 m2 °C/W. For wicking area, polyester blended with Tencel fabric demonstrated the highest wicking area whereas Tencel fabric displayed the highest WVTR of 1069.21 g/24h.m2 . Based on findings, Tencel bedsheet could offer better comfort in hot environment as the heat and water vapour can pass through the fabric easily compared to other fabrics. Meanwhile, polyester bedsheet will offer better comfort in cold environment as it can retain the heat and this can help the users to feel warmer in cold environment.